Effects of organic and inorganic fertilizers on the growth, yield and nitrogen uptake by BRRI dhan28 - Islam, Md Rafiqul; Shawon, Aurunima Kanchi Suprova; Begum, Most Lutfun Nesa; Huda, Azmul (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Boro season of 2014 to evaluate the effect of integrated use of manures and fertilizers for maximizing the growth and yield of BRRI dhan28. The experiment was laid out in a randomized complete block design with six treatments and four replications. The treatments include T0 [Control], T1 [Soil Test Basis-Chemical Fertilizer], T2 [(Cowdung) + STB-CF] on IPNS basis, T3 [(Poultry Manure) + STB-CF] on IPNS basis, T4 [(Compost) + STB-CF] on IPNS basis, and T5 [Farmers practice]. The maximum grain yield of 4340 kg ha-1 (95.59% increase over control) and straw yield of 4024 kg ha-1 (56.42% increase over control) were recorded in T3 [ (PM) + STB-CF]. The lowest grain and straw yields were found for T0 (Control) treatment. The N, P, K and S contents and uptake by BRRI dhan28 were profoundly influenced due to combined application of manures and fertilizers. The performance of the treatment T3 was better than T1, T2 and T4 in producing the yield of grain and straw of BRRI dhan28 although they received the same amount of nutrients. The results indicate that application of fertilizers in combination with poultry manure could be considered more effective in rice production. So, the treatment T3 can be used for the successful cultivation of BRRI dhan28. Res. Agric., Livest. Fish.3(1): 99-104, April 2016